Fixation of femoral fractures with titanium plate and screws: a pilot study in rats - Jennifer Tsi Gerber; Gabrielle Grosko Kuchar; Suyany Gabriely Weiss; Fernanda Tiboni; Luana Mordask Bonetto; Paola Fernanda Cotait Corso; Thaís Costa Casagrande; Rafaela Scariot (Revista Sul-Brasileira de Odontologia, 2021)
The repair of bone defects is a study model that has been used in several experiments to analyze the influence of surgical and pharmacological approaches aiming to improve bone regeneration. Mechanical stimulus is a crucial factor in the healing process. Therefore, a variety of measures exists to aid in bone repair by using different methods of immobilization and fixation. Objective: To delineate an unprecedented technique of stable bone fixation with titanium plates and screws in rat femoral fracture. Material and methods: Six Wistar rats underwent surgical procedures for complete femur fracture and fixation with titanium plates and screws, in six different combinations. The rats were divided into two subgroups, according to the technique applied: fixation performed after the bone fracture, and fixation performed before fracture induction. The animals were euthanized 45 days after the procedure, and the femur was evaluated clinically and radiographically. Results: There was a failure of the fracture fixation in the majority of the animals, except in rat 6, which had a good stability of the bone stumps and satisfactory bone repair. Conclusion: The best technique was with a four-hole titanium plate and four screws of the 2-mm system, with the fixation of the material prior to fracture induction.